2010
DOI: 10.1080/09540121.2010.484456
|View full text |Cite
|
Sign up to set email alerts
|

HIV-infected patients and treatment outcomes: an equivalence study of community-located, primary care-based HIV treatment vs. hospital-based specialty care in the Bronx, New York

Abstract: The HIV-infected population in the U.S. is expanding as patients survive longer and new infections are identified. In many areas, particularly rural/medically-underserved regions, there is a growing shortage of providers with sufficient HIV expertise. HIV services incorporated into community-based, primary care settings may therefore improve the distribution and delivery of HIV treatment. Our objective was to describe/compare patients and treatment outcomes in two settings: a community-located, primary care-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 21 publications
6
41
1
Order By: Relevance
“…The majority were retrospective cohort (n = 12) (Assefa et al, 2012;Backus et al, 2010;Chan et al, 2011;Chu, Umanski, Blank, Grossberg, & Selwyn, 2010;Fatti, Grimwood, & Bock, 2010;Kerr et al, 2012;Kitahata et al, 2003;Landon et al, 2005;Odafe, Idoko, et al, 2012;Odafe, Torpey, et al, 2012;Sherr et al, 2010;Solomon, Flynn, & Lavetsky, 2005) or cross-sectional studies (n = 7) (Anaya, Yano, & Asch, 2004;Boyer et al, 2011;Horberg, Hurley, Silverberg, Kinsman, & Quesenberry, 2007;Saha et al, 2013;Shet et al, 2011;Wilson, Landon, Hirschhorn, et al, 2005). One study had a prospective cohort design (Sangsari et al, 2012), and eight studies did not explicitly state their design strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The majority were retrospective cohort (n = 12) (Assefa et al, 2012;Backus et al, 2010;Chan et al, 2011;Chu, Umanski, Blank, Grossberg, & Selwyn, 2010;Fatti, Grimwood, & Bock, 2010;Kerr et al, 2012;Kitahata et al, 2003;Landon et al, 2005;Odafe, Idoko, et al, 2012;Odafe, Torpey, et al, 2012;Sherr et al, 2010;Solomon, Flynn, & Lavetsky, 2005) or cross-sectional studies (n = 7) (Anaya, Yano, & Asch, 2004;Boyer et al, 2011;Horberg, Hurley, Silverberg, Kinsman, & Quesenberry, 2007;Saha et al, 2013;Shet et al, 2011;Wilson, Landon, Hirschhorn, et al, 2005). One study had a prospective cohort design (Sangsari et al, 2012), and eight studies did not explicitly state their design strategy.…”
Section: Resultsmentioning
confidence: 99%
“…More recent work has shown that generalists with either HIV experience or formalized specialist decision support perform equally as well as HIV specialists for ART management. 7,21,37 Physicians in our study practiced in a variety of settings, and potentially reflect a more real-world experience of care delivery to people with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has shown that generalists with either HIV experience or formalized specialist decision support perform equally as well as HIV specialists for ART management. 7,21,37 Physicians in our study practiced in a variety of settings, and potentially reflect a more real-world experience of care delivery to people with HIV.We have previously demonstrated that patients cared for with models in which specialist physicians managed the majority of HIV care had lower rates of cancer screening. 24 As hypothesized, in this study, we found that family physician HIV experience did not influence these primary care outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations